2020
DOI: 10.15244/pjoes/120387
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Recreation and Tourism Use Value of Bozcaada by Travel Cost Analysis Methods

Abstract: In this study, Travel Cost Analysis is used to make an economic valuation of recreational area for the Bozcaada, NW Turkey. Within this framework, a total of 200 questionnaires were applied to the visitors at Bozcaada by the random sampling method. In the economic analysis model of Bozcaada, the "Number of Visits" made to the area per year was taken as the dependent variable, while "Travel Expenses", "Participants' Level of Income", "Age of participants" and "Vehicle Ownership Status" were taken as independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…According to Zhang Xiang-rang, the rural tourism developed in the glass village of Pinggu District, Beijing, has had a positive effect on the local culture, economy, and management. The authors in [ 13 ] selected different research perspectives and used a combination of qualitative and quantitative analysis methods to study in depth the relationship between cultural heritage and rural tourism from the perspectives of villagers, tourists, and researchers, respectively, and concluded that rural tourism can contribute to cultural heritage. The authors in [ 14 ] researched the Three Gorges Chexi Folklore Scenic Area in the field and analyzed the influence of local residents on rural tourism using resident perception theory.…”
Section: Related Workmentioning
confidence: 99%
“…According to Zhang Xiang-rang, the rural tourism developed in the glass village of Pinggu District, Beijing, has had a positive effect on the local culture, economy, and management. The authors in [ 13 ] selected different research perspectives and used a combination of qualitative and quantitative analysis methods to study in depth the relationship between cultural heritage and rural tourism from the perspectives of villagers, tourists, and researchers, respectively, and concluded that rural tourism can contribute to cultural heritage. The authors in [ 14 ] researched the Three Gorges Chexi Folklore Scenic Area in the field and analyzed the influence of local residents on rural tourism using resident perception theory.…”
Section: Related Workmentioning
confidence: 99%
“…A zoned travel cost approach can be used to estimate the economic value of ecotourism [18][19][20]. The use of the travel cost method for the valuation of tourism objects is also used by [21] in Bozcaada (Turkey), [22] in Valencia (Spain), and [23] in Taman Tasik Cempaka (Malaysia). The stages in calculating the economic value of ecotourism [24][25][26][27][28] are as follows: To determine the socioeconomic factors that influence the intensity of travel visits, multiple linear analysis is used.…”
Section: Travel Cost Analysismentioning
confidence: 99%
“…The travel cost method is based on the demand theory, which assumes that the demand for a recreational destination (a natural or cultural one) is inversely related to the travel costs that a visitor is willing to pay as a result of assessing its characteristics [19,20,[32][33][34][35]. Moreover, travel cost analysis is carried out to assess the benefits generated by cultural heritage elements: a price per visit that "reveals" visitors' willingness to pay (accommodation, entrance fees, and transport) to enjoy cultural goods [19,20,33,34].…”
Section: Background Literaturementioning
confidence: 99%
“…Heritage properties are a particular category of goods that are not bought and sold on ordinary markets [19,31], the economic valuation of which is performed indirectly by estimating the value of use that falls within the nonmarket valuation using revealed preference methods [9,11,20,21,[32][33][34]. Assessing the use value is not easy because historical buildings have characteristics such as uniqueness and irreversibility [21], as well as a wide range of values that are impossible to measure in monetary terms (e.g., social value) [11,20].…”
Section: Introductionmentioning
confidence: 99%